Use of conjunctions as cohesive devices in argumentative writing of Jordanian EFL learners - Salman Al-Shamalat, Rawhi Yousef (2022)
Cohesive devices are one of the components of conjunction devices that tie the elements of a written text together and make it cohesive. Effective use of cohesive devices will produce cohesion in the text. English as foreign language learners face some challenges in the use of cohesive devices effectively in their writing. Previous studies showed that Jordanian EFL students face difficulties in the use of cohesive devices which prevents them creating a cohesive text. The present research draws upon Halliday and Hassan’s (1976) Taxonomy of Cohesive Devices. It examines the types of conjunctions, the correlation between undergraduates’ correct use of conjunctions and their proficiency, the correlation between correct use of conjunctions and overall quality of writing, the most common conjunction errors in argumentative essays written by EFL undergraduates, andJordanian EFL learners finally EFL teachers’ perceptions on how using conjunctions can improve undergraduates’ argumentativ writing quality. This mixed-method study included sixty (n=60) undergraduates at the Dept. of English Language and Literature at Mu’tah University in Jordan. The participants of the study were selected purposively. The study used text and thematic analysis of learners’ essays to see how cohesively learners write argumentative essays. The data were analysed using a variety of analysis in SPSS such as Frequency test, Chi-square, Pearson’s correlation test and thematic analysis. The density and accuracy of cohesive devices and related ideas such as text unity, content, logical order, content, and the writer’s background knowledge were examined. The research was mainly qualitative, but it correspondingly entailed a quantitative component. It used the triangulation of varied sources of data: participants’ groups (teachers and students) and two research instruments including semi-structured interviews and text analysis. The findings of this study showed that Jordanian EFL undergraduates frequently used the following types of conjunctions, respectively: additive, adversative, causal and temporal in which additives are the most used. In addition, the findings revealed that the presence and absence of conjunctions affected the overall cohesion of the written essays that relates to a considerable number of errors including semantic misuse, syntactic misuse, stylistic misuse, mechanical misuse, redundancy, omission, unnecessary addition, and positional misuse of conjunctions. The findings showed that there is a need for developing and enhancing their undergraduates’ writing quality where most of the chosen writing samples entailed different kinds of syntactic misuse and conjunctions’ underuse. The research provides a detailed discussion of its results concerning its context and the main body of research in the field. It emphasizes investigating cohesion and understanding its accuracy in argumentative essays. The results of this study provide some significant pedagogical implications for the teaching of English as a foreign language. The study will help the curriculum designers, mainly authors of writing materials and English language textbooks in EFL settings, to present such cohesive devices/ conjunctions in teaching materials more effectively for classroom purposes. Finally, this study provides some significant recommendations that notify practice, decision-making, and further investigations.